Aktivitas Larvasidal Ekstrak Etanol Biji Pepaya (Carica papaya) dan Daun Mindi (Mella Azedarach) - Agus Saputra; Dewi Fesbayati Lestari Djungu; Emerlinda P. Gelalan (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
Helminthiasis is an adverse disease. This disease is caused by parasites such as trematodes, cestodes, and nematodes. The search for bioactive compounds from various plants that have anthelmintic activity is carried out by various researchers. Papaya seeds and mindi leaf have been known as a good plants for health. Various studies shown that extracts water, ethanol and chloroform have activity for antimicrobial, antilipidemia, antidiabetic and antiparasitic. In this study the extraction of secondary metabolites from mindi leaf and papaya seeds was carried out for larvicidal activity. From the results of extraction with ethanol, the yields of mindi leaf and papaya seeds were obtained 19.97% and 12.97% respectively. Phytochemical analysis shows that both extracts have the same class of compounds tannins, saponins, phenolhydroquinones, flavonoids, and alkaloids. The difference is in the concentration of tannin and saponin mindi leaf higher than papaya seeds. In testing larvicidal activity, the extract of mindi leaf had a stronger activity compared to papaya seeds. Extract mindi leaf 15% has the strongest activity of killing larvae at ± 25 minutes. This activity is stronger than extract papaya seed 15% which is ± 125 minutes or with albendazole 0.03%, ± 46 minutes